Comparative Analysis of Antioxidant Potential in Hexane and Methanol Fractions of Sungkai Leaves - Deswita, Elvira; Imelda, Imelda; Suryati, Suryati (Universitas Pendidikan Mandalika, 2025)
This study aimed to compare the antioxidant potential of hexane and methanol fractions of sungkai (Paronema canescens Jack) leaves from Tanah Datar Regency, West Sumatra, Indonesia. The methanol extract was then fractionated using hexane and ethyl acetate. Total phenolic content was determined using the Folin-Ciocalteu method and antioxidant activity was evaluated using the DPPH (2,2-diphenyl-1-picrylhydrazyl) assay. According to the conducted research, the methanol fraction exhibits a significantly higher total phenolic content, quantified at 92.22 mg GAE/g, in contrast to the hexane fraction, which recorded a content of 25.33 mg GAE/g. Furthermore, the methanol fraction demonstrated robust antioxidant activity, with an IC50 value of 75.425 mg/L, whereas the hexane fraction demonstrated comparatively weaker antioxidant activity, with an IC50 value of 232.595 mg/L. The strong antioxidant activity of the methanol fraction can be attributed to its high content of phenolic compounds, such as flavonoids and tannins, which are known to possess potent antioxidant properties. The synergistic effects of these compounds may further enhance the overall antioxidant capacity of the methanolic fraction. In conclusion, the methanol fraction of sungkai leaves from Tanah Datar Regency demonstrates superior antioxidant potential compared to the hexane fraction, suggesting its potential as a natural source of antioxidants for various applications.